Causal Relationship between Economic Growth and Macroeconomic Interactions - Abel, Sanderson; Mauto, Respect Kudzai; Jeke, Leward; Manenge, Robson (International Journal of Economics and Financial Issues, 2025)
This study examines the causal relationship between economic growth and the interplay of money supply, interest rate, and gross domestic product growth rate in five African nations (Botswana, Namibia, South Africa, Zambia, and Zimbabwe) using panel data from 2010 to 2024. Employing Granger causality method, the results reveal no significant causal link between economic growth and the interactions of these monetary variables. This suggests that changes in money supply, interest rates, and GDP growth rate do not predict changes in economic growth, and vice versa. The findings have important implications for policymakers, indicating a more complex relationship between economic growth and monetary variables than previously assumed. The absence of causality may imply that other factors, such as institutional or structural elements, play a more crucial role in driving economic growth in these countries